2011
DOI: 10.1108/15982681111158724
|View full text |Cite
|
Sign up to set email alerts
|

Assessing quality gap of university services

Abstract: Purpose -The purpose of this paper is to determine the quality gap of university services in the behavioral science faculties of the University of Tehran (Iran). Design/methodology/approach -In the current research, 300 students of five behavioral science faculties -Psychology and Educational Science, Social Science, Economics, Physical Education and Sport Science, Management, Entrepreneurship -in the University of Tehran (Iran), were chosen randomly and completed the SERVQUAL questionnaire. This questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…In a study conducted by Ruby, there were negative quality gaps in four dimensions (reliability, assurance, responsiveness and empathy), but there was a positive quality gap in the tangible dimension; in this dimension, students' expectations of the educational services quality were lower than their perceptions (11). In Abili study, there were negative quality gaps in three dimensions (tangible, reliability and empathy) (12). Negative quality gaps in educational services mean students' perceptions are lower than their expectations, indicating the dissatisfaction of students.…”
Section: Discussionmentioning
confidence: 88%
“…In a study conducted by Ruby, there were negative quality gaps in four dimensions (reliability, assurance, responsiveness and empathy), but there was a positive quality gap in the tangible dimension; in this dimension, students' expectations of the educational services quality were lower than their perceptions (11). In Abili study, there were negative quality gaps in three dimensions (tangible, reliability and empathy) (12). Negative quality gaps in educational services mean students' perceptions are lower than their expectations, indicating the dissatisfaction of students.…”
Section: Discussionmentioning
confidence: 88%
“…Arambewela and Hall (2013) indicated that student satisfaction profoundly influenced by the service quality. Recent service quality literature confirmed that the influence of service quality towards satisfaction (Abili et al, 2011;Fernandes et al, 2013). One study reveals that satisfaction is affected by service quality and service quality is passing through perceived value in tertiary education setting (Brown and Mazzarol, 2009).…”
Section: Student Satisfactionmentioning
confidence: 97%
“…Obtaining responses from the students is a must to manage service quality. Feedback is highly useful for evaluation and improvement (Abili, Thani, Mokhtarian, & Rashidi, 2011). Recently, measuring student satisfaction in the education sector has become compulsory (J.…”
Section: Introductionmentioning
confidence: 99%